Nucleotide sequence and expression of the gene encoding the EcoRII modification enzyme. - Som, S (1987)
The gene coding for the EcoRII modification enzyme has been cloned and the nucleotide sequence of 1933 base pairs containing the gene has been determined. The gene codes for a protein of 477 amino acids. Two transcriptional start sites have been mapped by S1 mapping. One deletion that removes 34 N-terminal amino acids was found to have partial enzyme activity. Comparison of the EcoRII methylase sequence with other cytosine methylases revealed several domains of partial homology among all cytosine methylases. Cloning the gene in multicopy pUC vectors increased the expression by 6-18 fold. A 40 fold overproduction of the EcoRII methylase was obtained by cloning the gene in the expression vector carrying the lambda PL promoter.